1951
DOI: 10.1139/v51-110
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Alpha-Ketols in the Low-Sugar Redox Recipe for Low Temperature Emulsion Copolymerization

Abstract: I t was found.that the induced deconlposition of peroxy co~llpounds c o~~l d lead to faster rates of polymerization or practical rates of polymerization a t lower tcmperat~tres. In Germany polymerization recipes were developed containing a pefosy conlpound in the oil phase, a reducer in the aqueous phase and a metal carrler. 'This idea was transferred to America after the war and became the basis of the present recipes used i n the production of cold rubbers. As reducers the most comn~only used appear to be di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1972
1972
1972
1972

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 37 publications
(44 reference statements)
0
1
0
Order By: Relevance
“…The reduction of ferric iron in water-logged soils has been attributed to microbial activity, but Takai and Kamura (1966) have reported evidence of the chemical reduction of iron with reduced organic products that resulted from the anaerobic decomposition of the organic amendment. Other workers in basic organic chemistry research have demonstrated the reduction of ferric iron to ferrous with various types of sugars (Orr and Williams, 1951). In the mechanisms, it was suggested that sugar and ferric iron formed a complex that resulted in the formation of sugar free radicals, which subsequently reduced the remaining ferric iron.…”
Section: Resultsmentioning
confidence: 99%
“…The reduction of ferric iron in water-logged soils has been attributed to microbial activity, but Takai and Kamura (1966) have reported evidence of the chemical reduction of iron with reduced organic products that resulted from the anaerobic decomposition of the organic amendment. Other workers in basic organic chemistry research have demonstrated the reduction of ferric iron to ferrous with various types of sugars (Orr and Williams, 1951). In the mechanisms, it was suggested that sugar and ferric iron formed a complex that resulted in the formation of sugar free radicals, which subsequently reduced the remaining ferric iron.…”
Section: Resultsmentioning
confidence: 99%